2017
DOI: 10.1073/pnas.1701829114
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional manipulation of mTOR signaling disrupts socially mediated vocal learning in juvenile songbirds

Abstract: Early life experiences can have long-lasting behavioral consequences because they are encoded when the brain is most malleable. The mechanistic target of rapamycin (mTOR) signaling cascade modulates experience-dependent synaptic plasticity, among other processes. mTOR has been almost exclusively examined in adult rodent learning models, but may be especially important in organizing neural circuits required for developmental acquisition of meaningful complex behaviors. It is among the most commonly implicated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(56 citation statements)
references
References 60 publications
2
53
1
Order By: Relevance
“…We hypothesize that rapamycin acted by inactivating mTOR, but this needs to be tested directly. Together with the results of Ahmadiantehrani and London (), our results show that the PI3K‐Akt‐mTOR signaling pathway plays an important role in mediating plasticity in the avian forebrain. Our study demonstrates that the avian song system provides an excellent model for investigating nongenomic mechanisms by which sex steroids have neuroprotective effects in the context of naturally occurring neurodegeneration in adult brains.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…We hypothesize that rapamycin acted by inactivating mTOR, but this needs to be tested directly. Together with the results of Ahmadiantehrani and London (), our results show that the PI3K‐Akt‐mTOR signaling pathway plays an important role in mediating plasticity in the avian forebrain. Our study demonstrates that the avian song system provides an excellent model for investigating nongenomic mechanisms by which sex steroids have neuroprotective effects in the context of naturally occurring neurodegeneration in adult brains.…”
Section: Discussionsupporting
confidence: 87%
“…In fact, rapamycin has actually been reported to be neuroprotective in different models (Cai & Yan, ; Su, Li, Jia, & Zhuo, ). Ahmadiantehrani and London () found that the number of cells immunoreactive to phosphorylated S6, an mTOR target protein, in forebrain auditory regions of juvenile male zebra finches returned to baseline levels by 15 hr following infusion of rapamycin, which further suggests that it is not toxic to cells. Rapamycin is being used in clinical anti‐aging studies in humans, without the adverse side effects that would be expected if it is neurotoxic (Kraig et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors also discovered that social interactions were impaired (as measured by how much time the juveniles spent close to and facing their tutors, who were in adjacent cages) in finches that experienced an enhancement of mTOR via SC79 administration. This finding is consistent with other studies on constitutive increases in mTOR expression and social interactions (6).…”
Section: Mtor Tutors and Song Memoriesmentioning
(Expert classified)
“…To investigate the hypothesized role played by mTOR in the regulation of song learning from a tutor, Ahmadiantehrani and London (6) took advantage of what is known about intraspecific variation in the song-learning process in zebra finches. First, unlike many other songbird species, in zebra finches only males learn the speciestypical song, though males and females can produce calls (5).…”
Section: Mtor Tutors and Song Memoriesmentioning
confidence: 99%
See 1 more Smart Citation